Implementation of the Marketing Strategy of PT Bintang Sayap Utama Malang in order to Expand Market Share - Sugeng Riani; Mulyono Mulyono; Dharmayanti Pri Handini (International Journal of Economics, Management and Accounting, 2024)
This study aims to determine and analyze how the marketing strategy is carried out by PT. Bintang Sayap Utama in Malang in expanding market share. The data analysis technique used by the researcher is quantitative descriptive analysis used to determine the marketing mix, internal and external environment, using SWOT analysis, and to support the use of quantitative analysis in the IFE, EFE, IE, and AHP matrices. The results of the study indicate that the main priority criteria considered by experts in expanding market share is product development. The main priority alternative considered by experts in product development is to carry out distribution cost efficiency.